2016
DOI: 10.1186/s12875-016-0527-7
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities treated in primary care in children with chronic fatigue syndrome / myalgic encephalomyelitis: A nationwide registry linkage study from Norway

Abstract: BackgroundChronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is a complex condition. Causal factors are not established, although underlying psychological or immunological susceptibility has been proposed. We studied primary care diagnoses for children with CFS/ME, with children with another hospital diagnosis (type 1 diabetes mellitus [T1DM]) and the general child population as comparison groups.MethodsAll Norwegian children born 1992–2012 constituted the study sample. Children with CFS/ME (n = 1670)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Other quantitative studies identified included two database studies [ 27 , 28 ] a review of medical records [ 29 ], and an evaluation of a training programme [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other quantitative studies identified included two database studies [ 27 , 28 ] a review of medical records [ 29 ], and an evaluation of a training programme [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…An aberrant serological pattern of reactivity with individual EBV antigens has been found in some (11–21), but not in other (22–24) investigations. Besides EBV (9, 25) other herpesviruses that have been tentatively implicated in the pathogenesis, based on serology or nucleic acid detection, are human herpesvirus 6 [HHV-6A (26, 27), varicella-zoster virus (VZV) (28), cytomegalovirus (CMV), see e.g., (29), and HHV-7] (26). Although a direct causative effect of a herpesvirus may be unlikely (29), one or several of them may be involved in combinatorial pathogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Knight et al (2013) found that 51% of children and adolescents attending a specialist service reported having a comorbid disorder. Moreover, in a registry-linkage study of children and adolescents within the general population in Norway, Bakken et al (2016) found that a group with CFS were more likely to report a comorbid diagnosis than a group with type 1 diabetes, and a group from the general population. Comorbidities included anxiety, depression, diabetes, asthma and migraine.…”
Section: Introductionmentioning
confidence: 99%